Application of different Scheimpflug-based lens densitometry methods in phacodynamics prediction - Faria-Correia F (Dove Medical Press, 2016)
Fernando Faria-Correia,1–5 Bernardo T Lopes,5,6 Isaac C Ramos,5,6 Tiago Monteiro,1,2 Nuno Franqueira,1 Renato Ambrósio Jr5–8 1Ophthalmology Department, Hospital de Braga, Braga, Portugal; 2Life and Health Sciences Research Institute (ICVS), School of Health Sciences, University of Minho, Braga, Portugal; 3ICVS/3B’s - PT Government Associate Laboratory, Braga, Portugal; 4ICVS/3B’s - PT Government Associate Laboratory, Guimarães, Portugal; 5Rio de Janeiro Corneal Tomography and Biomechanics Study Group, Rio de Janeiro, Brazil; 6Instituto de Olhos Renato Ambrósio, Rio de Janeiro, Brazil; 7VisareRio, Rio de Janeiro, Brazil; 8Department of Ophthalmology and Visual Sciences, Federal University of São Paulo, São Paulo, Brazil Purpose: To evaluate the correlations between preoperative Scheimpflug-based lens densitometry metrics and phacodynamics. Methods: The Lens Opacities Classification System III (LOCS III) was used to grade nuclear opalescence (NO), along with different methods of lens densitometry evaluation (absolute scale from 0% to 100%): three-dimensional (3D), linear, and region of interest (ROI) modes. Cumulative dissipated energy (CDE) and total ultrasound (US) time were recorded and correlated with the different methods of cataract grading. Significant correlations were evaluated using Pearson or Spearman correlation coefficients according to data normality. Results: A positive correlation was detected between the NO score and the average density and the maximum density derived from the 3D mode (r=0.624, P<0.001; r=0.619, P<0.001, respectively) and the ROI mode (r=0.600, P<0.001; r=0.642, P<0.001, respectively). Regarding the linear mode, only the average density parameter presented a significant relationship with the NO score (r=0.569, P<0.001). The 3D-derived average density and maximum density were positively correlated with CDE (rho =0.682, P<0.001; rho =0.683, P<0.001, respectively) and total US time (rho =0.631 and rho =0.668, respectively). There was a linear relationship between the average density and maximum density of the ROI mode and CDE (rho =0.686, P<0.001; rho =0.598, P<0.001, respectively) and total US time (rho =0.642 and rho =0.644, respectively). The average density was the only parameter derived from the linear mode that showed a significant correlation with CDE (rho =0.522, P<0.001) and total US time (rho =0.450, P<0.001). Conclusion: Specific Scheimpflug-derived densitometric parameters of the nucleus correlated with phacoemulsification parameters. The use of the appropriate densitometry approach can predict more efficiently the phacodynamics. Keywords: cataract, phacoemulsification, scheimpflug, densitometry